Classification of greenhouses with flexible coating - Chebanov, L.; Kiyanovskiy, A.; Chebanov, T.; Lyashenko , I. (Ways to Improve Construction Efficiency, 2022)
The main types of modern greenhouses with a fence made of film (in one layer and double with an air layer) and polycarbonate are considered. Different methods of growing plants in natural and artificial substrates on trays, supports, and special tables are shown. The elements of galvanized constructions of complete factory readiness differ in height, span, pitch of columns, number and position of elm blocks. The structural features of such buildings and structures make it possible to create many volume-planning solutions for the implementation of various agronomic technologies when growing vegetables and flowers, as well as meeting the needs of production and sanitary and household needs of workers. Engineering and technological systems provide a comfortable micro-climate for plants at different times of the year. Passive ventilation is used (single and double butterfly type in the roof, in the side and end walls), as well as active with the possibility of air humidification The concept of energy saving allows you to store (accumulate) heat in the tanks (systems) of boiler houses, including during operation of boiler houses in the summer to obtain carbon dioxide. In greenhouses, pipes are arranged in the underground space to preserve the energy of warm air in winter and cool the air in summer. Special methods of cleaning drainage drains allow you to save and reuse nutrients during drip irrigation of various plants. The technology of building greenhouses involves the execution of works with sets of specialized machines, as well as universal machines with a set of interchangeable working bodies. For the mechanization of individual processes, special machines and mechanisms have been developed for welding of pipes, installation of foundations and elements of enclosing structures, etc.